Evaluation of Toraja (Indonesia) local aromatic rice mutant developed using heavy-ion beam irradiation - Andi Muliarni Okasa; Rinaldi Sjahril; Muhammad Riadi; Meta Mahendradatta; Tadashi Sato; Kinya Toriyama; Kotaro Ishii; Yoriko Hayashi; Tomoko Abe (Society for Indonesian Biodiversity, 2021)
Abstract. Okasa AM, Sjahril R, Riadi M, Mahendradatta M, Sato T, Toriyama K, Ishii K, Hayashi Y, Abe T. 2021. Evaluation of Toraja (Indonesia) local aromatic rice mutant developed using heavy-ion beam irradiation. Biodiversitas 22: 3474-3481. The aromatic local Toraja rice